Efficacy of a bacterial bedding conditioner in the reduction of footpad lesions in broilers - Galosi, Livio; Biagini, Lucia; Attili, Anna-Rita; Tambella, Adolfo Maria; Rossi, Giacomo; Provolo, Giorgio; Falconi, Roberto; Castiglione, Giulia; Roncarati, Alessandra (Frontiers in Veterinary Science, 2025)
Footpad dermatitis is a multifactorial condition that affects broiler welfare. We aimed to evaluate whether a bacterial compound sprinkled on the litter could have a positive effect on the formation of footpad lesions (FPL), a trial was conducted under productive conditions. A total of 89,200 Ross308 chickens (39 ± 3 g) were housed in two sheds (C, control; T, treated). Females were housed in the first part of each shed, and males in the second and third part. A bacterial bedding conditioner was applied in T, while no treatments were carried out in C. Females were slaughtered at 36d (T: 1528 ± 195 g; C: 1562 ± 188 g) and males utilized the whole space until 43d (T: 2696 ± 296 g; C: 2737 ± 364 g). At 20d and before capture, 30 birds living in each part of the shed were randomly selected and, from both pads, the perimeter shape of each lesion was recorded, and the FPL area was measured. Litter was sampled at the same timepoints, for bacteriological and mycological culture, and chemical analysis. At slaughtering, 12 legs for females and 12 for males, both C and T, were randomly selected for histological examination. At day 20, FPL were not observed in birds. At 36 days, lesions measured in T (0.57 ± 0.08 cm2) were significantly lower than in C (1.47 ± 0.14 cm2; p < 0.0001). At 44d, lesions measured in T (0.65 ± 0.18 cm2) were significantly lower than in C (1.76 ± 0.34 cm2; p = 0.049). In litter collected in T, a significant reduction was observed for Gram negative bacteria (p = 0.0015) and Staphylococcus spp. (p = 0.0386), particularly in the second part of the shed (p = 0.0098, p = 0.0131 respectively). Regarding FPL, birds farmed in T showed a total histological score significantly lower than in C (p = 0.0002), more specifically for males (p < 0.0001). The use of the compound positively affected width and severity of FPL, supported by bacteriological analysis that evidenced a reduction of the total charge of bacteria commonly involved in the disease.